« Solitaire ou solidaire » dans L’Exil et le Royaume d’Albert Camus - Fernando Gomes (Carnets)
Reading the short stories of L’Exil et le Royaume, we show that Camusian heroes are all faced with the "solitaire ou solidaire" dilemma, that they aspire to communicate with the other and the world, in short, to the kingdom, but face a triple isolation – geographical, political and psychological – which proves to be the essence of their exile. However, we find that, because he is placed in a different geopolitical context – South America and not the pre-war Algeria – the protagonist of "La Pierre qui pousse" escapes this fate, the isolation and loneliness that can lead to solidarity and even brotherhood.